The life cycle approach as an innovative methodology for the recovery and restoration of cultural heritage. Issue 2 (17th November 2014) - Settembre Blundo, Davide; Ferrari, Anna Maria; Pini, Martina; Riccardi, Maria Pia; García, José Francisco; Fernández del Hoyo, Alfonso Pedro
Abstract : Purpose: – In this paper, of exploratory character, the purpose of this paper is to propose the analysis of the life cycle for assessing the environmental, economic, and social impact in the activity of recovery, restoration, and valorization of Cultural Heritage. Design/methodology/approach: – The analysis protocol is applied to the case of recovery and restoration processes and then outlining the salient features of what may become a model of Cultural Heritage Life Cycle Management (CH-LCM). Findings: – The authors propose the approach of the life cycle, normally used to assess the impact of materials, processes or products, to the management of cultural heritage as an innovative methodology with great potential. Originality/value: – The methodology for this sector is highly innovative, especially in its interdisciplinary approach, through the use of different technical, historical, and economic skills which can provide the tools for the preparation of a management plan according to the logic of the life cycle.